Analysis of Zakat, Infaq, and Sadaqah (ZIS) Management in Mosque Zakat Collection Units (UPZ) in Palembang City - Dessy Carolina; M. Arief Apriansyah; Meilinda Anggreni; Tiara Nurpratiwi (Universitas Muhammadiyah Makassar, 2025)
Mosque Zakat Collection Units (UPZ) occupy a distinct strategic position, operating as grassroots collection centers and enjoying high communal trust. However, UPZ Mosques including the 369 officially registered units in Palembang City often operate within a duality: adhering to formal regulatory demands from BAZNAS while simultaneously managing limited human resources and organizational structures. This research aims to comprehensively analyze ZIS management practices within these Mosque UPZ in Palembang City. This study employed a descriptive qualitative approach utilizing a multiple case study design. The sample selection was conducted through Stratified Purposive Sampling, resulting in the selection of 18 Mosque UPZ representing variations in collection scale and location context. Primary data was gathered via in-depth interviews with key UPZ. The findings reveal significant heterogeneity in ZIS management practices among the sampled Mosque UPZ in Palembang City. While fundamental collection and local distribution activities generally align, primary challenges identified include inconsistent accountability systems (record-keeping and reporting) and limitations in certified human capital. UPZ with a large scale of collection tend to exhibit more structured and transparent management processes. ZIS management within Mosque UPZ in Palembang City requires strategic harmonization between community-based practices and formal accountability requirements. The practical implication of this study underscores the necessity for structured capacity building programs delivered by BAZNAS Palembang City. These programs should focus on improving financial literacy and standardized reporting among UPZ human resources.